Multilayer engineered nanoliposomes as a novel tool for oral delivery of lipopeptide-based vaccines against group A Streptococcus. (May 2016) - Marasini, Nirmal; Giddam, Ashwini K; Ghaffar, Khairunnisa A; Batzloff, Michael R; Good, Michael F; Skwarczynski, Mariusz; Toth, Istvan
Aim: To develop an oral nanovaccine delivery system for lipopeptide-based vaccine candidate against group A Streptococcus .Materials & methods: Lipid-core peptide-1-loaded nanoliposomes were prepared as a template and coated with opposite-charged polyelectrolytes to produce particles with size <200 nm. Efficacy of this oral nanovaccine delivery system was evaluated in mice model.Results: Polymer-coated liposomes produced significantly higher antigen-specific mucosal IgA and systemic IgG titers in comparison to vaccine formulated with a strong mucosal adjuvant upon oral immunization in mice. Moreover, high levels of systemic antibody titers were retained even at day 185 postprimary immunization.Conclusion: Efficient oral delivery platform for lipopeptide-based vaccines has been developed.